REDUCING BPD IN A LEVEL IV NICU. Issue 12 (18th November 2016) - Bartman, Thomas; Shepherd, Ed; Nelin, Leif; Dail, James; Holston, Margaret; Wishloff, Erin; Keels, Erin; Thomas, Leslie; Kuehne, Brandon; Larouere, Marissa; Elgin, Amee; Foor, Nick
Abstract : Background: The incidence of "any" and "severe" BPD in our all-referral unit was higher than comparison NICUs, even when controlling for NICU type, gestational age, and age at admission. Therefore, we initiated a QI project to improve adherence to best practices to reduce our iatrogenic contribution to the development of BPD. Objectives: In infants born before 30 weeks admitted to main campus before 29 days of life, to decrease the incidence of any BPD in survivors at DOL 28 from 78% to 62%, and of severe BPD in survivors at 36 weeks CGA from 62% to 48%, by 12/31/2015 and sustain indefinitely. Methods: Our multidisciplinary team identified a number of practice/system drivers (shown in attached key driver diagram). Upon these we layered a frame addressing the three physiologic drivers of BPD: barotrauma, atelecto-trauma, and oxygen toxicity. We developed protocols to address these three drivers (one shown in attachment). After multiple PDSAs, a marketing blitz ("stand-down"), emphasizing a wingman approach, was necessary before change started to occur. Results: Shortly after the stand-down "any" BPD, and a few months later "severe" BPD, each showed statistical improvement. Time to first extubation attempt declined as well. We continue to work on PDSAs to reduce hyperoxia. (all shown in attachment) Conclusions: Multiple contextual factors were leading to our high BPD rate, including lack of a burning platform and a sense of "it is someone else's problem". Reducing BPD required addressing the physiologic causes of disease as well as these cultural factors.Figure 1 Figure 2 Figure 3 Figure 4 Figure 5 Figure 6